Controlled-Release Oxycodone and Naloxone in the Treatment of Chronic Low Back Pain: A Placebo-Controlled, Randomized Study. (2013) - Cloutier, C; Taliano, J; O'Mahony, W; Csanadi, M; Cohen, G; Sutton, I; Sinclair, D; Awde, M; Henein, S; Robinson, L; Eisenhoffer, J; Piraino, PS; et al.
Abstract : BACKGROUND: For Canadian regulatory purposes, an analgesic study was required to complement previously completed, pivotal studies on bowel effects and analgesia associated with controlled-release (CR) oxycodone/CR naloxone. OBJECTIVES: To compare the analgesic efficacy and safety of CR oxycodone/CR naloxone versus placebo in patients with chronic low back pain. METHODS: Patients requiring opioid therapy underwent a two- to seven-day opioid washout before being randomly assigned to receive either 10 mg/5 mg CR oxycodone/CR naloxone or placebo every 12 h, titrated weekly according to efficacy and tolerability to 20 mg/10 mg, 30 mg/15 mg or 40 mg/20 mg every 12 h. After four weeks, patients crossed over to the alternative treatment for an additional four weeks. Acetaminophen/codeine (300 mg/30 mg every 4 h to 6 h as needed) was provided as rescue medication. RESULTS: Of the 83 randomized patients, 54 (65%) comprised the per-protocol population. According to per-protocol analysis, CR oxycodone/CR naloxone resulted in significantly lower mean (± SD) pain scores measured on a visual analogue scale (48.6±23.1 mm versus 55.9±25.4 mm; P=0.0296) and five-point ordinal pain intensity scores (2.1±0.8 versus 2.4±0.9; P=0.0415) compared with placebo. After the double-blinded phase, patients and investigators both preferred CR oxycodone/CR naloxone over placebo. These outcomes continued in the 79% of patients who chose to continue receiving CR oxycodone/CR naloxone in a six-month, open-label evaluation. CONCLUSIONS: In patients complying with treatment as per protocol, CR oxycodone/CR naloxone was effective for the management of chronic low back pain of moderate or severe intensity. Erratum to "Controlled-Release Oxycodone and Naloxone in the Treatment of Chronic Low Back Pain: A Placebo-Controlled, Randomized Study" dx.doi.org/10.1155/2013/407817